KESALAHAN BERBAHASA BIDANG FONOLOGI PADA VIDEO YOUTUBE “HELLO JADOO” DUBBING INDONESIA - Khasanah, Farinda (University of Brawijaya, 2024)
Language is the main tool used by humans to communicate and interact in everyday life. Language develops and changes over time according to the needs and dynamics of society. With language humans can convey ideas, feelings, and information with others in everyday life. Language errors can occur in spoken form. Dubbing or substituting voices in different languages on the Youtube video of the animated cartoon